The Use of Figures of Speech in Frost’s “Nothing Gold Can Stay” - Ulvia Ika Surya; Agus Wardhono; Hairus Salikin; Suryo Tri Saksono (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2022)
The poem “Nothing Gold Can Stay” by Robert Frost illustrates how fleeting life is. Its rhyme arrangement (aa bb cc) demonstrates the poem’s brilliance. Based on the usage of figures of speech, this analysis illuminates the poem’s meaning. From the analysis, it is found out that: First, Frost succeeds in using figures of speech proportionally. Second, Frost underscores that nothing in our lives—nothing ideal, lovely, youthful, or pure—can ever endure.